PEARL - THE NEW REGIONAL FORECASTING MODEL OF THE NETHERLANDS - Dik Leering; Andries Hans De Jong (European Regional Science Association (ERSA), 2005)
The Netherlands has a rather long history of developing models in the field of regional forecasts. Among othter things, these forecasts are used as an instrument for planning of house-building. In 2004 Statistics Netherlands and the Spatial Planning Bureau started with the development of a new model, called PEARL (which stands for 'Population Extrapolations At Regional Level'). It is an integrated model for the forecast of the population (by ethnic group) and households. PEARL will be used to regionalize the official forecasts of population (by ethnic group) and households at the national level, which are compiled by Statistics Netherlands. The lowest level of the regional forecasts will be the municipal level, which permits the aggregation to larger NUTS regions, such as 'COROP' and 'province'. The forecast-horizon of the regional forecasts will be 15 to 20 years, although computations for a longer period are possible. An important objective of PEARL is to be considered as the official regional forecast, from 2007 onwards. Assumptions on demographic (growth) components (fertility, mortality, internal and external migration) and transition rates (with respect to the life course) will be formulated at the municipal level. These assumptions are used as input for PEARL. In this way transparency of the outcomes of the model is promoted. In order to achieve consistency between population and households, PEARL consists of both a macro- and a micro-layer. At the macro-layer (the municipal level) the assumptions are applied, while in the micro-layer (individual level) the resulting events are administrated. In this way the micro-layer consists of approximately 16 million persons and approximately 7 million households. In switching between the macro- and the micro-layer PEARL distinguishes itself from more conventional models. The primary goal is to use PEARL as a (robust) instrument for forecasting. However, it may also be used as a tool for compiling scenarios. This can be done at the macro level (by formulating alternative assumptions at the municipal level), but also at the micro level (by using alternative figures on risks). In the last application PEARL is used as a micro-simulation model. The software program PEARL is written in Delphi-5. The intention is to publish first outcomes (with a limited scope) in the second half of 2005
Keywords: 330